Imaging Characterization Lumbar Disk Hernia in Operated patients. - Enrique Hernández Padrón; Félix Dueñas Ros (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: The details of lumbar disk hernia are specifically described in imaging studies, which leads to very specific diagnosis contributing to its appropriate treatment. Objective: To characterize through imaging studies the lumbar disk hernia in operated patients. Methods: Descriptive observational, correlational, retrospective study of a series of cases, carried out in the University Hospital "Dr. Gustavo Aldereguía Lima" of Cienfuegos, from 2000 to 2005, including all the patients who required imaging studies for a suspect of lumbar disk hernia, who received surgical treatment in that institution. The available imaging means were used: spine simple radiography in lumbar area, myelography and computerized axial tomography. Results: Males were more affected by lumbar disk hernia. The most common sings observed through spine simple radiography in lumbar area were: decrease of the intervertebral space and arthrosic changes in the vertebral bodies. Myelography was performed in six patients and three of them were positive. The most common kind of hernia according with their localization was the lateral, and according with the amount of herniated material, the protruded hernia. The most affected spaces were: L5- S1 and L4-L5. The patients of the third and fourth decade of life were the most affected, with a prevalence of the protruded hernia in the L5-S1 y L4 -L5 spaces. Conclusions: The imaging studies contributed to a correct characterization of lumbar disk hernia.